Progress in Ultrafast Intense Laser Science Volume V - Yamanouchi, Kaoru; Giulietti, Antonio; Ledingham, Kenneth; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
The PUILS series delivers up-to-date reviews of progress in Ultrafast Intense Laser Science, a newly emerging interdisciplinary research field spanning atomic and molecular physics, molecular science, and optical science, which has been stimulated by the recent developments in ultrafast laser technologies. Each volume compiles peer-reviewed articles authored by researchers at the forefront of each their own subfields of UILS. Every chapter opens with an overview of the topics to be discussed, so that researchers unfamiliar to the subfield, as well as graduate students, can grasp the importance and attractions of the research topic at hand; these are followed by reports of cutting-edge discoveries. This fifth volume covers a broad range of topics from this interdisciplinary research field, focusing on coherent responses of gaseous and condensed matter to ultrashort intense laser pulses, propagation of intense laser pulses, and laser-plasma interaction and its applications.
Vibrational and Electronic Excitation of Molecules by Short-Pulse Strong Laser Fields -- Coherent Lattice Oscillations in Solids and Their Optical Control -- Coherent Lattice Oscillations in Solids and Their Optical Control -- Heterodyne Interferometry Using High-Order Harmonic Generation in Mixed Gases -- Propagation of Ultrashort Pulses in Condensed Media -- On Lightning Control Using Lasers -- Advances in X-Ray Studies of Ultraintense Laser-Plasma Interactions -- High Field Photonics in Laser Plasmas: Propagation Studies, Electron Acceleration, and Nuclear Activation With Ultrashort Intense Laser Pulses -- Laser Plasma Acceleration and Related Electromagnetic Sources -- Laser-Driven Ion Generation with Short, Intense, and High Contrast Pulses.
Keywords: Physics; Spectroscopy; Chemistry, Physical organic; Physics; Optics, Optoelectronics, Plasmonics and Optical Devices; Solid State Physics; Spectroscopy and Microscopy; Spectroscopy/Spectrometry.; Physical Chemistry